2017
DOI: 10.14311/ap.2017.57.0182
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the Gas Control in Ucg

Abstract: Underground Coal Gasification represents an alternative for conventional coal mining. This technology is also less expensive than traditional mining. It is expected that coal will be an important energy source in the coming decades. In requirement to improve the gasification process we must ensure that the combustion reactions generated enough energy to heat the reactants. This can be achieved by controlling the flow of oxidizing agents and the underpressure control at the exit of the reactor UCG. This paper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…Several experiments as trials of a real UCG were performed with the ex-situ reactor. This laboratory gasification equipment was well described in [41,42]. Similar trials of the UCG on a laboratory ex-situ reactor can be found in [43,44].…”
Section: Experimental Ucg In Ex-situ Reactormentioning
confidence: 76%
See 2 more Smart Citations
“…Several experiments as trials of a real UCG were performed with the ex-situ reactor. This laboratory gasification equipment was well described in [41,42]. Similar trials of the UCG on a laboratory ex-situ reactor can be found in [43,44].…”
Section: Experimental Ucg In Ex-situ Reactormentioning
confidence: 76%
“…Lignite coal from the Slovak mine that is suitable for the UCG was gasified. The composition of the coal that was gasified and factors that affect the UCG can be found in [41]. The influence of various gasification agents (i.e., its flows and pressures) on the syngas quality was discussed in [2].…”
Section: Experimental Ucg In Ex-situ Reactormentioning
confidence: 99%
See 1 more Smart Citation
“…The UCG process is complex and dynamic [45]. On the other hand, the position of active cavity moves forward continuously in the gasification process [46,47], it is not fixed like the surface gasification position. The gasified coal seam is superimposed and solidified, burning in situ, unlike surface gasification, which can break the coal body according to requirements, add feeding materials according to requirements, clean up coal ash in time, and be easily controlled.…”
Section: The Development Of Ucg Projects Worldwidementioning
confidence: 99%
“…Optimal control is the most investigated field in UCG within academic research. Much work focused on UCG control has been done on experimental ex-situ reactors (e.g., [24,30,31]) but also there are some trials on in-situ gasifier (e.g., [52]).…”
Section: Control Of Ucgmentioning
confidence: 99%